The role of ultrasound in engineering separation processes /c Rosli Mohd Yunus - Rosli Mohd. Yunus 1963- (Majlis syarahan umum profesor, 2012)
The presentation starts with a brief explaination on some of the separation processes that are commonly used in the industry